Asociación entre la morfología alar y el uso del hábitat en seis especies de palomas (Columbidae) neotropicales - Ocampo Vargas, Diego (2019)
Biomechanics, behavior, and natural history influence wing dimension and shape. Wing design often correlates with features of the habitat in which each species is found. Doves and pigeons (Columbidae family) range from long-distance fliers (e.g., canopy and open area species) to very short-distance fliers (e.g., species adapted to dense understory forests) and such variation makes this group fit to test the association between flying habits and wing morphology. Our objective in this study is to determine whether the wing morphology (shape and dimensions) of six dove species is associated to their flying capability. We predict that the long-distance fliers Patagioenas flavirostris and P. nigrirostris will have long and sharp wings; while the very short-distance flier Geotrygon montana will have broad and rounded wings. Other species (e.g., Leptotila verreauxi, L. cassini and Zenaida asiatica) whose flying capability fits in between these two will have wings with intermediate morphological features. We measured the wing disc loading, shape ratio, the ratio of mean to maximum wing chord, relative wing length, and wing area for each species. We conducted a discriminant function analysis to compare which variables explain better the differences in wing morphology across the six species, and used a binomial test to evaluate the power of the model. The model correctly classified 57 % of individuals within their own species. The flying capability is associated with the wing morphology of the six Columbidae species; with a wing design for long-distance fliers in P. flavirostris and P. nigrirostris, wing design for maneuvering in dense habitats in G. montana, and wings with an intermediate design in L. verreauxi, L. cassini and Z. asiatica.